Evaluation of Tpeak–Tend and QT intervals in Chagas’ Disease, Chronic Phase and Normal Electrocardiogram - Fragata Filho, Abilio Augusto; Fragata, Claudia da Silva; Lourenço, Angela Maria; Faccini, Cristiane Castro; França, João Ítalo Dias (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Introduction: Chagas’ disease lacks elements to predict which carriers will evolve into cardiac form and which will remain in undetermined form. Objective: To evaluate the relationship between electrocardiographic evolution and Tpeak–Tend and QT intervals, both corrected for heart rate, in chagasic patients with normal initial electrocardiogram. Method: Chagasic patients admitted to the institution until 2002 were retrospectively evaluated, and the electrocardiogram was normal at the first consultation. The Tpeak–Tend and QT intervals were measured in milliseconds at the V2 and V5 derivations, with the mean values corrected for heart rate (Bazett). The relationship of these values with the electrocardiographic evolution of the individuals was analyzed, considering the gender, time of evolution and whether they received benznidazole or not. Results: The corrected Tpeak–Tend interval showed no statistical significance among those who maintained or not normal electrocardiogram. The corrected QT interval, the treatment with benznidazole and the time of evolution showed significance for the maintenance of normal electrocardiogram. In the multivariate evaluation, treatment with benznidazole, the QTc interval and the time of evolution were independent variables for the maintenance of normal electrocardiogram. Conclusion: The Tpeak–Tend interval showed no predictor of electrocardiographic evolution. The increased QT interval favored changes.